The Stereotype of Working in Retailing as a Mediating Variable in Shaping the Perception of an Employer - Wanat , Tomasz (Studia Oeconomica Posnaniensia, 2014)
The aim of this paper is to assess the mediating effect of the stereotype of working in retailing on the perception of an employer. The paper assumed that the perception of an employer by the employees depends not only on the employer's CSR activities but also on the stereotype of working in retail held by the employees. Based on a sample of 262 retail employees, the mediating role of the stereotype was explored using the technique of bootstrapping. The findings of the study show that the stereotype of retail work can be treated as a moderator in shaping the perception of work in retailing. The paper contains the findings of research conducted as part of a project funded by the National Science Centre, granted on the basis of decision number DEC-2011/03/B/HS4/03576.